Glacial evolution of Sierra Nevada (Spain) and the origin of rock glaciares - Antonio Gómez Ortiz, David Palacios, Bogdan Palade, Lorenzo Vázquez Selem; Ferran Salvador Franch Luis Miguel Tanarro García, Marc Oliva Franganillo (Boletín de la Asociación de Geógrafos Españoles, 2013)
Resumen